2003
DOI: 10.2165/00128071-200304020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Ceramides and Skin Function

Abstract: Ceramides are the major lipid constituent of lamellar sheets present in the intercellular spaces of the stratum corneum. These lamellar sheets are thought to provide the barrier property of the epidermis. It is generally accepted that the intercellular lipid domain is composed of approximately equimolar concentrations of free fatty acids, cholesterol, and ceramides. Ceramides are a structurally heterogeneous and complex group of sphingolipids containing derivatives of sphingosine bases in amide linkage with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
257
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(265 citation statements)
references
References 170 publications
(161 reference statements)
2
257
0
6
Order By: Relevance
“…Major components of intercorneocyte lipids are ceramides, cholesterol and fatty acids, and it has been reported that ceramides play the essential role among them. 3,4 Skin diseases can cause abnormalities in the formation of intercorneocyte lipids. In particular, there have been reports of decreased ceramides in the stratum corneum in skin diseases with a damaged skin barrier, such as atopic dermatitis, 5,6 psoriasis 7 and ichthyosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major components of intercorneocyte lipids are ceramides, cholesterol and fatty acids, and it has been reported that ceramides play the essential role among them. 3,4 Skin diseases can cause abnormalities in the formation of intercorneocyte lipids. In particular, there have been reports of decreased ceramides in the stratum corneum in skin diseases with a damaged skin barrier, such as atopic dermatitis, 5,6 psoriasis 7 and ichthyosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramides are a structurally heterogeneous and complex group of sphingolipids containing derivatives of sphingosine bases in amide linkage with a variety of fatty acids with 24-26 carbon links. 4,32 Inside a cell, it has been reported that ceramides act as secondary signal transmitters and participate in the lipid signal paths in mammal cells, and induce cell proliferation and differentiation, restraint of cell cycle and apoptosis as major responses of intra-cell reaction to external stimulation. 33,34 Stratum corneum ceramides are heterogeneous compound mixtures.…”
mentioning
confidence: 99%
“…The FT-IR spectroscopy band in the 1738 -1646 cm -1 region originates from: the C=O stretch of monosubstituted amides like those found in N-acetylated GAG's [3], protein backbone (Protein Amide I) [6], ceramides [20], phospholipid esters [21] and the −COOH asymmetric vibrations [1]. Figure 2 shows the standard curve of the DS band in the 1738 -1646 cm -1 region that was used to quantify the corresponding FT-IR bands on the spectra of human skin (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The area of this band decreased by 35.60% (w/w) in the older group ( Table 1). Such band is made out of contributions from molecules known to increase with age like proteins [22], and from reactive carbonyl compounds that are believed to cause "the carbonyl stress" [23], minus reductions from molecules that decreased, such as GAG-N-acetyl groups [5,18] ceramides [20], and phospholipids [21]. The 35.60% (w/w) decrease of band intensity at 1738 -1646 cm -1 in the older group, indicates that there were more losses than gains in the number of molecules containing functional groups that absorb IR light in this region.…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated (Coderch et al, 2003;Bouwstra, Ponec, 2006) that formulations containing lipids identical to those in skin, in particular, some ceramide supplementation could have two divergent actions: (i) improve intercellular lamellae disorder or (ii) increase the skin lamellar phase, which could difficult the penetration of some drugs. These at first sight contradictory effects are dependent of the formulation that contains the ceramide.…”
Section: Resultsmentioning
confidence: 99%